CITRA PEREMPUAN DALAM IKLAN KECAP DI MEDIA MASSA - Susiyanah, Yuli (Islamic Communication Journal, 2019)
This article examines the image of women in soy sauce advertisements in the  mass media. In general, the image of them in the mass media is depicted by stereotypes and patriarchal cultures inherent in them. They are generally described as agents of domestic roles and sex objects, who must be discriminated and subordinated. The theory used in this paper is gender relationship and mass media with qualitative content analysis. The theory is applied to analyze the positions between men and women in order to realize gender equality. Using qualitative content analysis, ABC soy sauce ads “true husbands want to cook” shows that there is a reconstruction concept of the relationship between men and women from a stereotypical and patriarchal culture to be a culture of gender equality. In this advertisement, the domestic job that is identified with the duty and responsibility of woman being able to be reconstructed into a role that can be performed by all people including men. It can shape public opinion about the image of women who must not be discriminated in the mass media.